Changing of some parameters of the soil-plant system as an effect of different composts - Szabó, Anita; Berta-Szabó, Emese; Nagy, Péter Tamás; Balláné Kovács, Andrea; Vágó, Imtre (Acta Agraria Debreceniensis, 2010)
Composting is an alternative way for practicing site-specific and environmental friendly plant nutrient supply. Our aim was to study the effect of different composts on plant and soil system. Pot experiment with acidic sandy soil blended with three composts in five (0%, 5%, 10%, 25% and 50%) proportion was set up. Our experimental plant was perennial ryegrass (Lolium perenne L.). After the harvest of ryegrass we measured the fresh and dry weight of harvested plants, the P-, K-, Mg-contents, and the pH of soils.The three composts had different effect on dry weight production and on nutrient-supply of soil. We established that one of the compost had significantly larger effect on the dry weight of ryegrass compared to the others. In this study we proved that favourable compost/soil proportion is different in the case of different composts.